## Solve for x in the first equation, then solve the system using substitution. Write your answer as (x, y). 1103-03-02-00-00_v2_files/i

Question

Lorem ipsum dolor sit amet, consectetur adipiscing elit.Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu.Fusce viverra neque at purus laoreet consequa.Vivamus vulputate posuere nisl quis consequat.

## Answers ( No )

2x – 6y = 14

2x = 6y + 14

x = 3y + 7…..so sub in 3y + 7 for x in the other equation

4x – y = 9

4(3y + 7) – y = 9

12y + 28 – y = 9

12y – y = 9 – 28

11y = – 19

y = -19/11

x = 3y + 7

x = 3(-19/11) + 7

x = -57/11 + 7

x = -57/11 + 77/11

x = 20/11

solution is : (20/11, -19/11) <==